The Influence of Digital Marketing and Brand Awareness on Forming the Branding Image of Technology Companies - Ramadhanti Sugita, Frida Marischa; Handayani, Dr. Wiwik (International Journal of Scientific Research and Management (IJSRM), 2024)
The advancement of technology serves as a pivotal force driving transformation across diverse sectors, with technology companies assuming a central role in this evolution. The dynamic landscape of the digital age has significantly impacted technology firms, influencing the global business environment and shaping how companies operate, innovate, and interact with their clientele. The establishment and reinforcement of a brand image hold immense importance, influencing customers' purchasing decisions and fostering loyalty.                       For technology companies, the pivotal role of digital marketing and brand awareness in crafting their brand image cannot be overstated, allowing them to adapt to technological advancements and changing consumer preferences. The significance of brand awareness in molding consumer perceptions is crucial, where trust and understanding of the brand emerge as critical success factors. An optimal level of brand awareness contributes to the company's recognition as a prominent player in the industry, enhances customer loyalty, and provides a competitive edge. Within the context of this discourse, the primary aim of this study is to explore the influence of digital marketing and brand awareness on shaping the brand image of technology companies. This research employs a quantitative method utilizing a questionnaire approach supported by descriptive and causal methodologies. The assessment in this study involves the utilization of a Likert scale, capturing responses to statements gathered from 75 respondents. The sampling technique applied is the data analysis technique using Partial Least Squares. The findings of this research establish a correlation between digital marketing and brand awareness in shaping the branding image of technology companies.